Edwards curves based security authentication protocol for mobile RFID systems - Yu-long YANG; Chang-gen PENG; Zhou ZHOU; Xiao-pei ZHANG (Tongxin xuebao)
Existing work about RFID authentication protocols is usually difficult to adapt to mobile RFID systems.In order to solve the problem，an Edwards curves based security authentication protocol for mobile RFID systems is proposed.The protocol can improve the ability of resisting the side channel attacks by using the Edwards curve and the elliptic curve discrete logarithm problem is applied to implement safety certification.Further the tag and reader’s untraceable privacy is proved by using the provable security method，the security analysis shows that the protocol can be more effective against for various attacks which have existed.Compared with the existing structure similar to RFID authentication protocol，the protocol has better scalability and its security and performance is superior to other solutions.